El concepto de economía informal y su aplicación en México: factibilidad, inconvenientes y propuestas - Cervantes Niño, José Juan; Gutiérrez Garza, Esthela; Palacios, Lylia (El Colegio de México A.C., 2008)
On the basis of a historical review of ILO’s theoretical and methodological postulates for quantifying the informal sector from a global, regional (Latin America) and Mexican perspective, the authors argue the need to deal with a series of socio-economic disadvantages that prevent the application of the thesis of the informal economy in Mexico. This need is justified by proving that the methodology of the informal economy provides a far more accurate picture of informality in Mexico than that offered by traditional methodology; a number of strategies to encourage the implementation of this methodology are also proposed.